Co-Occurrence of Domestic Dogs and Gastropod Molluscs in Public Dog-Walking Spaces and Implications for Infection with Angiostrongylus vasorum: A Preliminary Study - Bryony A. Tolhurst; Andrew D. J. Overall; Peter J. King; Eric R. Morgan; Rowenna J. Baker (Animals, 2021)
Angiostrongylusvasorum is a helminth parasite of domestic dogs that is increasing in range and prevalence. Its lifecycle requires terrestrial gastropod mollusc (“gastropod”) intermediate hosts, but research is lacking regarding contact risk in situ. We studied co-occurrence between dogs and gastropods in dog-walking spaces in an A. vasorum hotspot in southern England, United Kingdom, with the aim of quantifying environmental and spatio-temporal overlap. We surveyed 390 quadrats and 180 point-counts along 3 km transects at seven sites, yielding 1672 gastropod and 763 dog observations. Common gastropods comprised Arion, Cornu, Monacha, Deroceras, Tandonia, Cochlicella, and Trochulus species. Habitat was the most important factor structuring both gastropod and dog presence and abundance. Likelihood ratio comparisons from conditional probability trees revealed that dogs were 15× more likely to be present on hardstanding surfaces than other habitats but were also present on natural and amenity grassland. Presence of gastropod species associated with high A. vasorum prevalence was 65.12× more likely in woodland/scrub and 62.17× more likely in amenity grassland than other habitats. For gastropods overall, high abundance was 5.82× more likely in woodland/scrub and natural grassland. The findings suggest co-occurrence is highest in amenity and natural grassland, but infection risk is greatest in amenity grassland and woodland/scrub.